Analysis Of Orthoptera in The Territory of Central Uzbekistan - Xusanova Ismigul Muzaffar qizi; Usmonjonova Ozoda Komiljon qizi (Zien Journals, 2023)
According to the geographical range of orthopteran insects of Central Uzbekistan, it belongs to 9 groups: Trans-Palaearctic species 24, European-Siberian species 7, European-Kazakh species 10, EuropeanCentral Asian species 6, Kazakhstan - Western Mongolian species 5, Kazakh-Mongolian species 5, Central Asian-Kazakh species 10, Central Asian species 32, Central Asian species. There are 12 species in Asia and Kazakhstan.
Keywords: Orthoptera; family; offspring; species